HUBUNGAN SAFETY INSPECTION DAN PENGETAHUAN DENGAN UNSAFE ACTION DI DEPARTEMEN ROLLING MILL - Intan Kristianti; Abdul Rohim Tualeka (The Indonesian Journal of Occupational Safety and Health, 2018)
There are millions of workplace accidents in the world with the loss of hundreds of billions annually. One of the direct causes of accidents due to unsafe action. It stems from the lack of control by the management and the basic causes in the form of individual factors. This study is conducted to look at the factors correlated with unsafe action in the Department of Rolling Mill PT. X Sidoarjo. The research was conducted by observation using cross-sectional design and a quantitative approach. Questionnaires were administered to 70 respondents who were drawn using simple random sampling technique. The variables studied were safety inspection, knowledge, and unsafe action. Data was presented in the form of frequency distributions and cross-tabulations then statistically analyzed using Spearman correlation. The study was conducted using α of 0.05. The results showed that the respondents had a good knowledge, safety inspection in PT. X had been executed well, and had a lower category of unsafe action. There were a correlation between knowledge with unsafe action (p= 0.028; r= -0.262), and a correlation between safety inspection with unsafe action (p= 0.015; r= -0.288). It can be concluded that the higher knowledge and safety inspection, the unsafe action would be lower. Keywords: knowledge, safety inspection, unsafe action